High temperature during pollination and its effect on grain corn yield - Reyes-González , Arturo; Reta-Sánchez , David Guadalupe; Sánchez-Duarte , Juan Isidro; Servín-Palestina , Miguel; Cueto-Wong, José Antonio (Ecosistemas y Recursos Agropecuarios, 2025)
The aim was to evaluate the effect of high temperature during the pollination stage on the grain corn yield in the Comarca Lagunera. The study was carried out in the spring 2023 growing season. Three corn hybrids (P3274W, H-383 and PATRIOTA) were evaluated under a subsurface drip irrigation system. The experiment was arranged as a randomized complete blocks design with three replicates. During crop development, extreme temperatures (40 °C) occurred during pollination for 11 days, starting at 74 and ending at 84 days after sowing (DAS). Due to the above, grain yields were low since they ranged between 0.76 and 2.5 t ha-1, which represented a reduction of 83 to 95% in the expected grain yield in corn.